A three-armed cryptand with triazine and pyridine units: synthesis, structure and complexation with polycyclic aromatic compounds - Lar, Claudia; Woiczechowski-Pop, Adrian; Bende, Attila; Grosu, Ioana Georgeta; Miklášová, Natalia; Bogdan, Elena; Hădade, Niculina Daniela; Terec, Anamaria; Grosu, Ion (Beilstein Journal of Organic Chemistry, 2018)
The aromatic nucleophilic substitution reaction based synthesis of a three-armed cryptand displaying 2,4,6-triphenyl-1,3,5-triazine units as caps and pyridine rings in the bridges, along with NMR, MS and molecular modelling-based structural analysis of this compound are reported. Appropriate NMR and molecular modelling investigations proved the formation of 1:1 host–guest assemblies between the investigated cryptand and some polynuclear aromatic hydrocarbons or their derivatives.
Keywords: aromatic guests; aromatic nucleophilic substitution; cryptand; NMR titration; 1,3,5-triazine

Supramolecular Chemistry - Steed, J. W.; Atwood, J. L. (Wiley & Sons, 2000)

(untitled) - Zhang, R.-F.; Hu, W.-J.; Liu, Y. A.; Zhao, X.-L.; Li, J.-S.; Jiang, B.; Wen, K. (J. Org. Chem., 2016)

(untitled) - Begel, S.; Scheurer, A.; Puchta, R. (J. Coord. Chem., 2015)

(untitled) - Zhang, M.; Yan, X.; Huang, F.; Niu, Z.; Gibson, H. W. (Acc. Chem. Res., 2014)

(untitled) - Crişan, C. V.; Terec, A.; Hădade, N. D.; Grosu, I. (Tetrahedron, 2015)

(untitled) - Wang, Q.; Cheng, M.; Zhao, Y.; Yang, Z.; Jiang, J.; Wang, L.; Pan, Y. (Chem. Commun., 2014)

(untitled) - Niu, Z.; Slebodnick, C.; Gibson, H. W. (Org. Lett., 2011)

(untitled) - Niu, Z.; Slebodnick, C.; Bonrad, K.; Huang, F.; Gibson, H. W. (Org. Lett., 2011)

(untitled) - Ashton, P. R.; Baldoni, V.; Balzani, V.; Credi, A.; Hoffmann, H. D. A.; Martinez-Diaz, M.-V.; Raymo, F. M.; Stoddart, J. F.; Venturi, M. (Chem. – Eur. J., 2001)

(untitled) - Qi, Z.; de Molina, P. M.; Jiang, W.; Wang, Q.; Nowosinski, K.; Schulz, A.; Gradzielski, M.; Schalley, C. A. (Chem. Sci., 2012)

(untitled) - Dale, E. J.; Vermeulen, N. A.; Thomas, A. A.; Barnes, J. C.; Juriček, M.; Blackburn, A. K.; Strutt, N. L.; Sarjeant, A. A.; Stern, C. L.; Denmark, S. E.; Stoddart, J. F. (J. Am. Chem. Soc., 2014)

(untitled) - Murase, T.; Otsuka, K.; Fujita, M. (J. Am. Chem. Soc., 2010)

(untitled) - Klosterman, J. K.; Yamauchi, Y.; Fujita, M. (Chem. Soc. Rev., 2009)

(untitled) - Singh, N.; Jo, J.-H.; Song, Y. H.; Kim, H.; Kim, D.; Lah, M. S.; Chi, K.-W. (Chem. Commun., 2015)

(untitled) - Clever, G. H.; Kawamura, W.; Tashiro, S.; Shiro, M.; Shionoya, M. (Angew. Chem., Int. Ed., 2012)

(untitled) - Xu, Z.; Huang, X.; Liang, J.; Zhang, S.; Zhou, S.; Chen, M.; Tang, M.; Jiang, L. (Eur. J. Org. Chem., 2010)

(untitled) - Paşcanu, V.; Cîrcu, M.; Socaci, C.; Terec, A.; Soran, A.; Grosu, I. (Tetrahedron Lett., 2013)

(untitled) - Pop, F.; Socaci, C.; Terec, A.; Condamine, E.; Varga, R. A.; Rat, C. I.; Roncali, J.; Grosu, I. (Tetrahedron, 2012)

(untitled) - Kocher, L.; Durot, S.; Heitz, V. (Chem. Commun., 2015)

(untitled) - Wang, L.; Wang, G.-T.; Zhao, X.; Jiang, X.-K.; Li, Z.-T. (J. Org. Chem., 2011)

(untitled) - Cîrcu, M.; Soran, A.; Hădade, N. D.; Rednic, M.; Terec, A.; Grosu, I. (J. Org. Chem., 2013)

(untitled) - Samanta, J.; Natarajan, R. (Org. Lett., 2016)

(untitled) - Wang, Q.; Zhang, C.; Noll, B. C.; Long, H.; Jin, Y.; Zhang, W. (Angew. Chem., Int. Ed., 2014)

(untitled) - Taesch, J.; Heitz, V.; Topić, F.; Rissanen, K. (Chem. Commun., 2012)

(untitled) - Li, S.; Liu, M.; Zheng, B.; Zhu, K.; Wang, F.; Li, N.; Zhao, X.-L.; Huang, F. (Org. Lett., 2009)

(untitled) - Britvin, S. N.; Rumyantsev, A. M.; Zobnina, A. E.; Padkina, M. V. (Chem. – Eur. J., 2016)

(untitled) - Kieryk, P.; Janczak, J.; Panek, J.; Miklitz, M.; Lisowski, J. (Org. Lett., 2016)

(untitled) - Naseer, M. M.; Wang, D.-X.; Zhao, L.; Huang, Z.-T.; Wang, M.-X. (J. Org. Chem., 2011)

(untitled) - Schneider, M. W.; Hauswald, H.-J. S.; Stoll, R.; Mastalerz, M. (Chem. Commun., 2012)

(untitled) - Schneider, M. W.; Oppel, I. M.; Mastalerz, M. (Chem. – Eur. J., 2012)

(untitled) - Wang, D.-X.; Wang, Q.-Q.; Han, Y.; Wang, Y.; Huang, Z.-T.; Wang, M.-X. (Chem. – Eur. J., 2010)

(untitled) - Woiczechowski-Pop, A.; Gligor, D.; Bende, A.; Varodi, C.; Bogdan, E.; Terec, A.; Grosu, I. (Supramol. Chem., 2015)

(untitled) - Wang, Z.; Luo, Y.; Zhai, T.-L.; Ma, H.; Chen, J.-J.; Shu, Y.; Zhang, C. (Org. Lett., 2016)

(untitled) - Matache, M.; Bogdan, E.; Hădade, N. D. (Chem. – Eur. J., 2014)

(untitled) - Okochi, K. D.; Han, G. S.; Aldridge, I. M.; Liu, Y.; Zhang, W. (Org. Lett., 2013)

(untitled) - Woiczechowski-Pop, A.; Dobra, I. L.; Roiban, G. D.; Terec, A.; Grosu, I. (Synth. Commun., 2012)

(untitled) - Hibbert, D. B.; Thordarson, P. (Chem. Commun., 2016)

(untitled) - Thordarson, P. (Chem. Soc. Rev., 2011)

(untitled) - Ulatowski, F.; Dabrowa, K.; Bałakier, T.; Jurczak, J. (J. Org. Chem., 2016)

(untitled) - Sherrill, C. D.; Takatani, T.; Hohenstein, E. G. (J. Phys. Chem. A, 2009)

(untitled) - Mishra, B. K.; Arey, J. S.; Sathyamurthy, N. (J. Phys. Chem. A, 2010)

(untitled) - Peverati, R.; Truhlar, D. G. (J. Phys. Chem. Lett., 2011)

(untitled) - Weigend, F.; Ahlrichs, R. (Phys. Chem. Chem. Phys., 2005)

Gaussian 09, Revision D.01 (Gaussian, Inc., 2009)

(untitled) - Tomasi, J.; Mennucci, B.; Cammi, R. (Chem. Rev., 2005)

(untitled) - Taylor, D. E.; Ángyán, J. G.; Galli, G.; Zhang, C.; Gygi, F.; Hirao, K.; Song, J. W.; Rahul, K.; von Lilienfeld, O. A.; Podeszwa, R.; Bulik, I. W.; Henderson, T. M.; et al. (J. Chem. Phys., 2016)